The Impact of Digital Nomad Economy on Local Businesses Study of MSME Market Changes in Popular Destinations in Indonesia - Qosim, Nanang; Rukmana, Arief Yanto; Usup, Usup (Eastasouth Institute, 2025)
This study examines the impact of the digital nomad economy on micro, small, and medium enterprises (MSMEs) in popular destinations in Indonesia, including Bali, Yogyakarta, and Lombok. Using a quantitative research approach, data were collected from 120 MSME owners and managers through a structured questionnaire measured on a 1-5 Likert scale. The findings, analyzed with SPSS version 25, reveal that the digital nomad economy creates significant opportunities for MSMEs, including revenue growth, an expanded customer base, and improved service quality. However, challenges such as increased competition, gentrification, and technological barriers were also identified. Regression analysis showed that adaptation strategies, customer engagement, and perceived challenges significantly influence business performance. This study underscores the need for capacity-building initiatives, inclusive growth policies, and enhanced access to technology to ensure sustainable benefits from the digital nomad economy for local MSMEs.